Non-invasive Electroencephalography Method Development and Validation using Carbamazepine - Murthy, Dr. S. Vasudeva (Asian Journal of Pharmaceutics (AJP), 2019)
Context: Recording of neurophysiological properties in a rodent model by stereotaxic surgery is well known, while the non-invasive method used to investigate the neurophysiological effects of studied using carbamazepine (CBZ). Aims: The effects of CBZ electrical activity of the brain recorded using a non-invasive technique and validated by an experiment involving stereotaxic surgery procedure are described in this paper. Settings and Design: To minimize painful procedures in rodents, an affordable technique was developed to record electroencephalogram (EEG) in the rodent model, and to the test drug molecules screened without giving any anesthetic agent. Methods and Materials: The present invention provides a disposable plastic foam EEG leads relates to a EEG component device for recording rat brain physiological changes in the form of EEG. This study was performed to quantify the pharmacodynamic properties of the CBZ. Rat surgery involving stereotaxic experiment used for validation process is described for the non-invasive method in this paper. Statistical Analysis Used: Paired t test used to calculate the differences in different EEG bands. Results: EEG analysis showed CBZ significantly increased in the delta and theta power and no effects on other the frequencies of the EEG. Similar observations were found in the invasive method of EEG in rats. Clinical and neurophysiological assessment using the simple, inexpensive technique of EEG observed. Conclusions: The results have shown CBZ induced a significant increase in slow activity waves represented by delta and theta waves. Administration of the carbamazepine in rats detected major neurological changes in the form of EEG and the technique of non-invasive EEG measurement found to be a useful tool to detect changes in the EEG.